Evaluation of serum leptin and adiponectin in obese individuals with chronic periodontitis - Ramanarayana Boyapati; Srikanth Chintalapani; Arpita Ramisetti; Shyam Sunder Salavadhi; Radhika Ramachandran (Wolters Kluwer Medknow Publications, 2018)
Objectives: Studies have reported changes in leptin and adiponectin levels in the gingival crevicular fluid, saliva, and blood serum of obese patients with periodontal disease. The aim of the study is to evaluate serum leptin and adiponectin levels in obese and nonobese individuals with chronic periodontitis and to deduce a relationship between the clinical parameters and the inflammatory biochemical parameters. Materials and Methods: In this case-control study, a total of fifty individuals were selected based on the body mass index (BMI): Group I of obese individuals with chronic periodontitis and Group II of nonobese individuals with chronic periodontitis. Periodontal parameters used in this study were plaque index, gingival index, probing pocket depth, and clinical attachment level. The effects of obesity and periodontal status on serum leptin and adiponectin levels of both groups were statistically analyzed using an independent t- test. Results: Statistical analysis showed that the effect of BMI on serum leptin and adiponectin levels was statistically significant (P < 0.01), and the effect of chronic periodontitis on the serum leptin and adiponectin levels was also statistically significant compared to nonobese individuals (P < 0.0001). However, there is no statistically significant correlation between serum leptin and adiponectin, which indicates that both are independent to each other. Conclusions: In obese individuals with chronic periodontitis, serum leptin levels were significantly high compared to nonobese individuals and serum adiponectin levels were significantly lower in obese individuals compared to nonobese individuals with periodontitis, though both the parameters were independent of each other.